PERAN LURAH DALAM MENINGKATKAN PELAYANAN PUBLIK DI KELURAHAN CONCONG LUAR KECAMATAN CONCONG KABUPATEN INDRAGIRI HILIR - jurnalmap map; Ngadirin ÔÇÄ; Hadi Susanto; Esa Wahyu Endarti (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to describe the influence of the role of the village head consisting of leadership, planning and supervision of public services partially or simultaneously in Concong Luar Subdistrict, Concong Subdistrict, Indragiri Hilir Regency. This type of research is explanatory research (explanatory research). The samples in this study were 35 people consisting of 9 village officials, 8 RW heads and 18 RT heads. The results showed that the variables of leadership, planning and supervision partially had a significant effect on public services in the Concong Luar Subdistrict, Concong Subdistrict, Indragiri Hilir Regency. The variables of leadership, planning, and supervision simultaneously have a significant effect on public services in the Concong Luar Subdistrict, Concong Subdistrict, Indragiri Hilir Regency.